2022
DOI: 10.1098/rspb.2021.2278
|View full text |Cite
|
Sign up to set email alerts
|

Postnatal expression of IGF2 is the norm in amniote vertebrates

Abstract: The insulin and insulin-like signalling (IIS) network plays an important role in mediating several life-history traits, including growth, reproduction and senescence. Although insulin-like growth factors (IGFs) 1 and 2 are both key hormones in the vertebrate IIS network, research on IGF2 in juveniles and adults has been largely neglected because early biomedical research on rodents found negligible IGF2 postnatal expression. Here, we challenge this assumption and ask to what degree IGF2 is expressed during pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 47 publications
0
10
0
Order By: Relevance
“…The results of this study showed that compared with WT siblings, mice with IGF2 overexpression showed significant increase in weight at 5-10 weeks of age. Previous studies ( 14 , 24 ) reported that a sex bias exists in the expression of IGF2, and the IGF2 level in females is significantly higher than that in males at the age of 5 years. Moreover, another study ( 25 ) found that hypoxic conditions lead to the upregulation of IGF2 expression in the placenta of female fetuses, while the hypoxic placenta of male fetuses shows no change.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…The results of this study showed that compared with WT siblings, mice with IGF2 overexpression showed significant increase in weight at 5-10 weeks of age. Previous studies ( 14 , 24 ) reported that a sex bias exists in the expression of IGF2, and the IGF2 level in females is significantly higher than that in males at the age of 5 years. Moreover, another study ( 25 ) found that hypoxic conditions lead to the upregulation of IGF2 expression in the placenta of female fetuses, while the hypoxic placenta of male fetuses shows no change.…”
Section: Discussionmentioning
confidence: 87%
“…Based on previous studies, it was determined that IGF1 has high postnatal expression ( 29 , 30 ) and that the expression of IGF2 is high during embryonic development but decreases to an undetectable level after birth ( 30 32 ). Several recent studies ( 12 – 14 , 24 , 33 ) have suggested that IGF2 is also expressed postnatally in humans and may play an important role in growth and development. Due to the previous opinion, there is currently a lack of related research on human postnatal IGF2 compared to studies on postnatal IGF1 ( 24 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fetal growth is regulated by the insulin-like growth factor system with IGF2 as a key factor ( 67 ). IGF2 is expressed in the adults of most amniotes (reptiles, birds and mammals), including human ( 153 ), whereas in mouse and rat Igf2 is expressed in placenta but is largely absent in adults. Both IGF2 and the M6P/IGF2R receptor are imprinted genes in most mammals including marsupials ( 154 ).…”
Section: Discussionmentioning
confidence: 99%
“…IGF-2 has been much less studied than IGF-1 but is expressed pre-and postnatally across amniotes, often at higher levels of expression than IGF-1 [102], and can stimulate growth and metabolism [103]. We might anticipate that changes in circulating hormone levels in the insulin/insulin-like signalling network would promote changes in total…”
Section: Endocrine Mechanisms and Climate Changementioning
confidence: 99%